Teachers' instructional and assessment methods for critical thinking skills and evaluation of the Hikmah Pedagogy Training modules: a case study in Kuala Lumpur - Hashim, Rosnani; Hussien, Suhailah; Wan Yusoff, Wan Mazwati; Khalid, Madihah; Hashim, Sulaiman; Zubairi, Ainol Madziah; Othman, Moomala (Centre for Teaching Thinking, Kulliyyah of Education, 2019)
The emphasis in twenty first century learning has shifted from concern over the output or product of learning, the so called knowledge, to the concern over the process of learning. It is not so much about facts anymore because in the age of information and communication technology, these can be obtained fast and easily by browsing in the internet. Beside fact, the internet can also provide video clips from Youtube which can be used for clearer illustration in the classroom. Thus, what are needed now are the skills of acquisition of data, organizing and applying it. Twenty first century learning requires critical and creative thinking skills, collaborative and communication skills, and most important of all, the caring thinking skill which will help us become useful local and global citizens. The problem or research question is, whether our school system is gearing up for this change? Have schools changed their ways of instruction and assessment? The purpose of the study is to examine teachers’ methods of instruction and assessment for enhancing critical skills. Specifically, the study investigates if the use of the Hikmah Pedagogy enhance the 21st century learning skills or the 5 Cs – critical, creative, collaborative, communicative and caring. The study was conducted in two primary and two secondary schools in the Wilayah Persekutuan involving 4 teachers in each school with the exception of one where 5 teachers participated. The study took place between June and November 2016. The study began with a pre-interview with each individual teacher, and teaching observation of selected teachers. This was followed with a two day training for the teachers on the nature and application of the Hikmah Pedagogy. Finally, teachers were guided to apply the Pedagogy in one of their classes in the first month. The teachers were selected based on the subjects of: English, Malay, moral education, Islamic education, science, and mathematics. The study applied a mixed method research design. The qualitative data were obtained from teachers and students using individual interviews and focus group discussion. The quantitative data from students were obtained using pre-post test for the UKMCTT for reasoning skills, the students’ self-assessment of their cognitive behaviours, the teacher’s assessment of students cognitive behaviour. The quantitative data from teachers were obtained using the MSG Thinking Styles, and The Critical and Creative Thinking Test. The findings revealed that in general the teachers had a good understanding of CT and assessment for CTS as evident from the interview and the CCTS pre and post scores. There was a qualitative difference in teachers’ instruction after the intervention using Hikmah Pedagogy. Both teachers and students were positive about the Hikmah Pedagogy for active learning that is student-centred. The two day teacher iii training was found to be useful although it could be further improved. The result of the UKMCTT showed a significance difference in students’ Reasoning skills in both primary and secondary levels. The successful classes were those with double exposure due to two subjects, and also the teachers who had conducted the class many times using the correct way. The cognitive behaviour checklist assessed by teachers showed that both primary and secondary students improved in reasoning and listening and speaking but not in metacognition and manners in the community of inquiry. The data on MSG thinking styles was not conclusive. Finally, teachers reported some major problems especially with time constraint and inability to cover the syllabus.